6‐Formylindolo[3, 2‐b]carbazole (FICZ) is a Very Minor Photoproduct of Tryptophan at Biologically Relevant Doses of UVB and Simulated Sunlight1. (12th July 2018) - Youssef, Antonia; von Koschembahr, Anne; Caillat, Sylvain; Corre, Sebastien; Galibert, Marie‐Dominique; Douki, Thierry
Abstract: Exposure to solar UV is at the origin of numerous photodegradation pathways in biomolecules. Tryptophan is readily modified by UVB radiation into ring‐opened and oxidized photoproducts. One of them, 6‐formylindolo[3, 2‐b]carbazole (FICZ), has been extensively studied in the recent years because it very efficiently binds to AhR, a major factor in numerous biologic processes, such as metabolism of xenobiotics. Unfortunately, little information is available on the actual yield of FICZ upon exposure to low and biologically relevant doses of UV radiation. In the present work, we used a sensitive and specific HPLC‐tandem mass spectrometry assay to quantify a series of photoproducts induced by UVB and simulated sunlight (SSL) in solutions of tryptophan. FICZ represented only a minute amount of the photoproducts (0.02 and 0.03%, respectively). Experiments were repeated in culture medium where the yield of FICZ was also found to be very low, even when Trp was added. Last, no FICZ could be detected in cytosolic fractions of cultured cells exposed to SSL. Altogether, the present results show that FICZ is a very minor photoproduct and that it cannot be considered the only endogenous photoproduct responsible for the induction of AhR‐dependent responses in UV‐irradiated cells. Abstract : FICZ is a tryptophan photoproduct that receives much attention because of its possible role in the UV‐induction of AhR‐mediated pathways. We report that FICZ is a very minor degradation product of tryptophan following exposure to low doses of either UVB or simulated sunlight.